Kedudukan dan Konsep Pertanggungjawaban Artificial Intelegence Dalam Hukum Positif Indonesia - Hardiyanti Qurrahman, Shofika; Ayunil, Safira; Aurelia Rahim, Tsabita (UNES Law Review, 2024)
Artificial intelligence, or better known as AI, in a technological era like this, is developing very rapidly. AI was created and designed to hamper the human brain, digging information, providing information, even solving problems. With AI designed just like humans, when AI commits an act against the law and causes loss, then AI cannot be brought to criminal responsibility. AI can not commit an offence independently, in its operation requires human help. In positive law in Indonesia, AI is not a legal subject like human beings and legal bodies that are jurisprudently recognized as legal subjects.